2007
DOI: 10.1002/ajmg.a.31612
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial anomalies, humero‐radial synostosis, rhizomelic limb shortness: Previously unrecognized autosomal recessive syndrome

Abstract: Humero-radial synostosis (HRS) is a rare skeletal anomaly that might be seen in some craniosynostosis syndromes, notably Antley-Bixler syndrome, and in other disorders in association with skeletal anomalies. Here we report on two daughters of first cousin Saudi parents with syndromic HRS. Both patients had distinctive craniofacial features including cranium bifidum occultum, hypertelorism, epicanthus inversus, capillary hemangiomata, and malformed ears. Musculoskeletal examination revealed rhizomelic shortness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Guilherme et al () reported two siblings with HRS and other anomalies, which appear to be a separate entity from any of the above syndromes. Al‐Hassnan and Teebi () categorized HRS into five groups: craniosynostosis, symphalangism, limb reduction, with other skeletal defects, and secondary teratogens.…”
Section: Discussionmentioning
confidence: 99%
“…Guilherme et al () reported two siblings with HRS and other anomalies, which appear to be a separate entity from any of the above syndromes. Al‐Hassnan and Teebi () categorized HRS into five groups: craniosynostosis, symphalangism, limb reduction, with other skeletal defects, and secondary teratogens.…”
Section: Discussionmentioning
confidence: 99%
“…HRS occurs in association with microcephaly in a number of multiple malformation syndromes [Ramer and Ladda, 1989]. In a recent review Al‐Hassnan and Teebi [2007] concluded that syndromic HRS can be categorized into five groups: (i) craniosynostosis syndromes, (ii) symphalangism syndromes, (iii) limb reduction syndromes, (iv) syndromes with other skeletal defects, and (v) those secondary to teratogens. It is difficult to classify our cases into any one of these specific categories because our patients showed an overlap with 4 different syndromes specifically; Antley and Bixler [1975], Pfeiffer [1964] and specially Ives and Houston [1980] and Keutel et al [1970] syndromes (Table II).…”
Section: Discussionmentioning
confidence: 99%